Image formation properties of As₄₀S₂₀Se₄₀ thin layers in application for gratings fabrication - Stronski, A.V.; Vlcek, M.; Shepeliavyi, P.E.; Sklenar, A.; Kostyukevich, S.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The present paper is concerned with investigations of image formation properties of As₄₀S₂₀Se₄₀ thin layers. Spectral dependence of the refraction index, n, of variously treated (virgin, exposed, annealed) samples was estimated from optical transmission in the spectral region 400 -2500 nm. The n energy dependence of variously treated samples was fitted by the Wemple-DiDomenico dispersion relationship and used to estimate the single-oscillator model parameters. It was found that exposure as well as annealing leads to the increase in n values over the all investigated spectral region. Changes of the parameters of the single-oscillator model induced by treatment are discussed on the base of photo- and thermally- induced structural changes, which were directly confirmed by Raman scattering measurements. Such photoinduced structural changes provide good etching selectivity of As₄₀S₂₀Se₄₀ layers in nonaqueous amine based solvents. The sensitivity values obtained on 488 nm wavelength consisted ~ 9 cm²/J. Surface relief patterns that were fabricated have good surface quality. Diffraction efficiency values of holographic diffraction gratings (HDG) obtained on the base of As₄₀S₂₀Se₄₀ layers consisted 60-70 %. Relief profile of HDG was close to sinusoidal one. High quality polymer HDG copies were obtained. AFM profiles of the initial replica copies were practically identical to the profile of the master grating.